2013
DOI: 10.5755/j01.eee.19.3.2690
|View full text |Cite
|
Sign up to set email alerts
|

Application of Arbitrary Position and Width Pulse Trains Signals in Ultrasonic Imaging: Correlation Performance Study

Abstract: Ultrasonic imaging requires both the accuracy and the resolution. Conventional imaging systems use the pulse signals to accomplish the task. But the energy attainable with such signals is limited. Spread spectrum, compressible signals allow to achieve the wide bandwidth even using long durations. Conventional signals do not offer full flexibility or, like nonlinear frequency modulation signals, lack the ease of properties control. We suggest using novel spread spectrum signals generation technique: trains of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…APWP signals offer the possibility to match the bandwidth of the ultrasonic transducer or even the whole signal transmission channel. Investigation presented in [13] has indicated that APWP signals can be optimized to produce correlation sidelobes that are lower than those of the pulse signal (Fig. 3).…”
Section: Apwp Signalsmentioning
confidence: 99%
See 3 more Smart Citations
“…APWP signals offer the possibility to match the bandwidth of the ultrasonic transducer or even the whole signal transmission channel. Investigation presented in [13] has indicated that APWP signals can be optimized to produce correlation sidelobes that are lower than those of the pulse signal (Fig. 3).…”
Section: Apwp Signalsmentioning
confidence: 99%
“…Then, this signal is used to obtain the auto-correlation function (AKF), submitted to analysis block to extract correlation properties discussed in section II and is stored in codes data base if it produces better correlation parameter than previous signal. The selected APWP codes can be used later in imaging applications [14] as optimal for a particular system-transducer combination.…”
Section: System Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Most widely used signals are chirp, linear frequency modulation and coded sequences [12]. New class of SS signals was suggested recently [15]: trains of pulses of arbitrary pulse width and position (APWP). For single reflection the SS signals have clear advantage: both sharp main correlation lobe and high energy increase the estimation accuracy.…”
Section: Introductionmentioning
confidence: 99%